Variables Associated with Ultra-Processed Foods Consumption among Brazilian Adolescents: A Systematic Review - Paulo Henrique Guerra; Evelyn Helena Corgosinho Ribeiro; Rafael Fagundes Lopes; Laura Maria Balestreri Nunes; Isis Carolina Viali; Brígida da Penha Ferraz; Inaiá Aparecida de Almeida; Milena Huber Garzella; Jonas Augusto Cardoso da Silveira (MDPI AG, 2023)
Background: Considering its deleterious effects on health, as well as the importance of information to support actions, strategies, and public policies, the present study was developed, aiming at identifying and classifying the main variables associated with ultra-processed foods consumption in Brazilian adolescents. Data sources: Targeting observational studies involving samples of Brazilian adolescents (11 to 19 years old), which evaluated possible associations between the consumption of ultra-processed foods and individual, interpersonal, environmental, and public policy variables, in October 2022, a systematic review was conducted, consulting electronic databases (Lilacs, Pubmed, Scielo, Scopus, and Web of Science), Google Scholar, and the reference lists of included articles. Data synthesis: The descriptive synthesis consisted of 11 papers, representing nine original studies. The main variables identified were: sedentary behavior (specially screen time), studying at a private school, having a higher body mass index, and being female. Conclusions: Based on this evidence, it is important to direct actions, strategies, and public policies aimed at confronting the consumption of ultra-processed foods for these groups.